ECONOMIC GROWTH IN THE REPUBLIC OF AZERBAIJAN AND COOPERATION WITH UNITED NATIONS - F. Damirli (Наука и техника)
Large reserves of hydrocarbon resources in the Caspian Sea and usage of these resources have allowed the Republic of Azerbaijan to become a country with rapidly growing world economy. Investment of large financial resources  in the development of infrastructure and non-oil sector has given a positive impulse to the development of the country’s economy. A great role in the implementation of various projects in Azerbaijan has played collaboration with various UN organizations in the country.